Quantifying research hotspots and trends in brucella spondylitis: a bibliometric analysis - Gu, Zhangui; Yang, Zongqiang; Fei, Le; Wei, Daihao; Ma, Long; Liu, Qiang; Shi, Jiandang (Frontiers in Surgery, 2025)
BackgroundHuman brucellosis is the most common bacterial zoonosis worldwide, with brucella spondylitis (BS) being one of its most severe forms, potentially leading to spinal deformity or paralysis. This study aims to provide a comprehensive overview of the current status and research trends in the BS field using bibliometric methods.MethodsPublications on BS from January 1, 1980, to March 24, 2024, were retrieved from the Web of Science database. We used Biblioshiny, VOSviewer, Scimago Graphica, CiteSpace, and Microsoft Office Excel Professional Plus 2016 to analyze publication frequency, geographic distribution, institutional affiliations, international collaborations, authorship, journal sources, keyword usage, trends, and cited references.ResultsBetween January 1, 1980, and March 24, 2024, 197 publications on BS were analyzed. Turkey emerged as the leading contributor, with 62 publications, accounting for 31.47%. Weibin Sheng was the most prolific author, contributing 7 papers (3.55%). Xinjiang Medical University was the leading institution with 13 documents (6.60%). Medicine and Rheumatology International each published 6 papers (3.05%). CiteSpace analysis highlighted “spinal brucellosis,” “spondylitis,” “complications,” “diagnosis,” and “involvement” as the core research areas in BS. Keyword clustering analysis identified 11 primary clusters representing the main research directions. Analysis of abstracts and keyword trends revealed that post-2020, emerging research frontiers include “instrumentation,” “management,” and “debridement.”ConclusionThere has been significant progress in BS research, with a steady increase in publications. Current research focuses on diagnosis and complications, while future studies may explore management and instrumentation. Increased collaboration among countries and researchers is recommended.